Good and real : demystifying paradoxes from physics to ethics - Drescher, Gary L. (MIT Press, 2006)
Examining a series of provocative paradoxes about consciousness, choice, ethics, and other topics, Good and Real tries to reconcile a purely mechanical view of the universe with key aspects of our subjective impressions of our own existence.